The macrophage‐related biomarkers sCD163 and sCD206 are released by different shedding mechanisms. Issue 5 (26th June 2019) - Nielsen, Marlene Christina; Andersen, Morten Nørgaard; Rittig, Nikolaj; Rødgaard‐Hansen, Sidsel; Grønbæk, Henning; Moestrup, Søren Kragh; Møller, Holger Jon; Etzerodt, Anders
Abstract: The hemoglobin receptor CD163 and the mannose receptor CD206 are both expressed on the surface of human macrophages. Upon inflammatory activation, the receptors are shed from the macrophage surface generating soluble products. The plasma concentration of both soluble CD163 (sCD163) and soluble CD206 (sCD206) are increased in several diseases, including inflammatory conditions and cancer. Here, we show that in contrast to CD163, LPS‐mediated shedding of CD206 in humans is slow and a result of indirect signaling. Although both sCD163 and sCD206 were increased in response to LPS stimulation in vivo, only CD163 was shed from LPS‐stimulated macrophages in vitro. Although both sCD163 and sCD206 were released from cultured macrophages stimulated with zymosan and PMA, shedding of CD206 was generally slower and less efficient and not reduced by inhibitors against the major protease classes. These data indicate that CD163 and CD206 are shed from the macrophages by very different mechanisms potentially involving distinctive inflammatory processes. Abstract : Differences in shedding patterns (and mechanisms) identified between macrophage‐related biomarkers sCD163 and sCD206.